2022
DOI: 10.1155/2022/4497176
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Hybrid Complexes of High- and Low-Molecular-Weight Hyaluronan Intradermal Injections for the Treatment of Skin Roughness and Laxity of the Neck

Abstract: This study aimed to evaluate the efficacy of a well-characterized formulation of hyaluronic acid (HA), Profhilo®, in the treatment of roughness and laxity of the neck skin. The study was performed on 25 subjects ranging in age from 40 to 65 years. Two injections of the studied product at 30-day intervals were performed, with evaluations conducted 1 and 4 months after the first injection. The efficacy was determined by clinical and multilevel instrumental evaluations. In addition, at the end of the study, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 30 publications
1
14
0
Order By: Relevance
“…The patented NAHYCO ® technology enables the delivery of HCC comprising low and high molecular weight HA characterized by increased stability and resistance to hyaluronidase degradation, 22 and its ability to sustain skin cell vitality and proliferation. 22,24 Moreover, HCC (commercial name, Profhilo ® ) demonstrated efficacy in clinical studies for improving facial appearance 25 and counteracting skin laxity 26 with a high safety profile. 27 This monocentric study aimed to evaluate the efficacy and tolerability of Profhilo Structura ® (a new formulation containing a higher concentration of HA; 45 mg/mL) injected into the lateral cheek fat compartment in a cohort of 50 healthy female subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The patented NAHYCO ® technology enables the delivery of HCC comprising low and high molecular weight HA characterized by increased stability and resistance to hyaluronidase degradation, 22 and its ability to sustain skin cell vitality and proliferation. 22,24 Moreover, HCC (commercial name, Profhilo ® ) demonstrated efficacy in clinical studies for improving facial appearance 25 and counteracting skin laxity 26 with a high safety profile. 27 This monocentric study aimed to evaluate the efficacy and tolerability of Profhilo Structura ® (a new formulation containing a higher concentration of HA; 45 mg/mL) injected into the lateral cheek fat compartment in a cohort of 50 healthy female subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, three independent in vivo studies, performing two facial subcutaneous injections with a 4-week time lapse between them, resulted in a significant improvement in facial face hydration, elasticity, and transepidermal water loss (TEWL), as well as in high patient satisfaction and optimal physician evaluations [ 30 , 31 , 32 , 33 ]. Importantly, HCC benefits were present in the absence of local side effects, as demonstrated by post-marketing surveillance data [ 31 ] and by long-term safety studies [ 34 ]. Moreover, treatment with HCCs proved to be effective not only for White populations, but also for different ethnicities.…”
Section: Medical Aesthetics Applicationsmentioning
confidence: 99%
“…Goltsova et al [ 35 ] and Satardinova et al [ 36 ] demonstrated significative amelioration of skin texture and hydration in the Russian and Oriental Mongolian population. Furthermore, a recent clinical study also proved that HCC treatment is effective in improving the facial appearance of Asian women, even earlier compared to White women [ 37 , 38 ].…”
Section: Medical Aesthetics Applicationsmentioning
confidence: 99%
See 2 more Smart Citations